Clinical Efficacy and Safety of Human Mesenchymal Stem Cell Therapy for Degenerative Disc Disease: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (14th September 2021) - Xie, Baocheng; Chen, Shichun; Xu, Yongxiang; Han, Weichao; Hu, Runkai; Chen, Minyi; He, Ruirong; Ding, Shaobo
Abstract : Degenerative disc disease (DDD) can cause severe low back pain, which will have a serious negative impact on the ability to perform daily tasks or activities. For the past few years, mesenchymal stem cell (MSC) transplantation has emerged as a promising strategy for the treatment of DDD. However, the clinical efficacy of MSC in the treatment of DDD still lacks clinical evidence and is controversial. We conducted a meta-analysis with randomized controlled trials (RCTs) to evaluate the clinical efficacy and safety of MSC transplantation in patients with DDD. We searched major databases using terms from the database's inception through March 2021. The Cochrane bias risk assessment tool was used to assess quality. The analysis showed that MSC therapy could decrease visual analog scale (VAS) scores (SMD = − 0.50, 95 % CI = − 0.68 ~ − 0.33, P < 0.00001 ) and Oswestry Disability Index (ODI) scores (SMD = − 0.27, 95 % CI = − 0.44 ~ − 0.09, P = 0.003 ). The outcomes with subgroup analysis showed that MSC therapy could decrease VAS scores in 3 months (P = 0.001 ), 6 months (P = 0.01 ), 12 months (P = 0.02 ), and ≥24 months (P = 0.002 ) and ODI scores in ≥24 months (P = 0.006 ). Pooled analysis showed that MSC therapy has a higher ratio of patients at most thresholds but particularly at the MIC (minimally important change) (P = 0.0002 ) and CSC (clinically significant change) (P = 0.0002 ) in VAS and MIC (P = 0.0005 ) and CSC (P = 0.001 ) pain responders in ODI. Adverse events (AE) of treatment-emergent adverse events (TEAE), back pain, arthralgia, and muscle spasms were not statistically significant between the two groups. However, our further statistical analysis showed that MSC therapy may induce AE of TEAE related to study treatment (OR = 3.05, 95 % CI = 1.11 ~ 8.40, P = 0.03 ). In conclusion, this study pooled the main outcomes and showed that MSC therapy could significantly decrease VAS and ODI scores in patients with DDD. Distinctly, the findings of this meta-analysis suggest a novel therapeutic strategy for patients with chronic low back pain (LBP) and lumbar dysfunction by DDD.